1995
DOI: 10.1016/0168-5597(94)00317-8
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic function and P300 amplitude in major depressive disorder (P300 and catecholamines)

Abstract: The neurobiology of P300 is still a subject of controversy. P300 amplitude appears to be modulated by multiple neurotransmitter systems, especially dopaminergic, noradrenergic as well as cholinergic and GABAergic. In this study, we investigated the relationship between P300 amplitude and catecholaminergic neurotransmission as assessed by the growth hormone (GH) response to clonidine and apomorphine challenges in 20 major depressive patients. Results showed a correlation of P300 amplitude with the apomorphine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 10 publications
2
20
0
3
Order By: Relevance
“…This finding is similar to the report that P200 amplitude was greater in depressive patients than in normal controls [15]. It is suggested that neurotransmitters, such as serotonin, catecholamines, and GABA, play a role in the generation of AERPs [16][17][18], and hence that disturbances in these neurotransmitter systems could be involved in the alterations in AERPs in SD. Another interesting finding from the present study is the significant interactive effects or interactive tendencies between order of days (SD) and TD on sleepiness, fatigue, and negative mood.…”
Section: Discussionsupporting
confidence: 80%
“…This finding is similar to the report that P200 amplitude was greater in depressive patients than in normal controls [15]. It is suggested that neurotransmitters, such as serotonin, catecholamines, and GABA, play a role in the generation of AERPs [16][17][18], and hence that disturbances in these neurotransmitter systems could be involved in the alterations in AERPs in SD. Another interesting finding from the present study is the significant interactive effects or interactive tendencies between order of days (SD) and TD on sleepiness, fatigue, and negative mood.…”
Section: Discussionsupporting
confidence: 80%
“…Like other substances of abuse, nicotine activates the mesolimbic dopamine system, and this effect appears to be essential for the reinforcing properties of nicotine (Ashton and Golding 1989;Nisell et al 1995). Vulnerability to both smoking and alcoholism may be mediated by common alterations of brain neurotransmission systems that influence P300 amplitude, a conclusion supported by evidence that dopamine is involved in the neu-rophysiological mechanisms which generate and/or modulate P300 (Stanzione et al 1991;Hansenne et al 1995).…”
Section: Discussionmentioning
confidence: 71%
“…(2) The dopamine antagonist sulpiride increases P300 in low-amplitude subjects and decreases it in high-amplitude subjects (Takeshita and Ogura, 1994). (3) Pharmacological studies have found dopaminergic mediation of P300 amplitude and latency (Hansenne et al, 1995;Wang et al, 2000). (4) Children at elevated risk for alcoholism demonstrate dopamine-related genetic differences and P300 amplitude deficits (Hill et al, 1998), which may be associated with an "endophenotype of alcoholism" that likely originate from externalizing disorders (cf.…”
Section: Dual-transmitter Hypothesismentioning
confidence: 99%